Examining public speaking anxiety and intervention strategies in rural Sarawak: a community-based perspective - Nik Fauzi, Sheela Faizura; Johari, Aiza; Rijeng, Jacqueline Susan; Sarkawi, Adib; Bujan, Azlina (Faculty of Administrative Science and Policy Studies, 2023)
Entrepreneurial communities in the rural areas of Sarawak are recognized for their distinctive local products which highlight an imperative need for effective market outreach. Mastery in product presentation is crucial for both face-to-face and digital marketing platforms. This study probes into the widespread phenomenon of public speaking anxiety among these communities particularly in the context of oral product pitching. It examines the repercussions of this anxiety on presentation skills and identifies interventions to ameliorate public speaking shortcomings. Adopting a quantitative research methodology, the study collects data through tailored questionnaires from small business owners in Sri Aman which represent the study's sample. Results indicate that public speaking anxiety is prevalent among these rural entrepreneurs due to cultural barriers and a scarcity of skill-building opportunities. This study is pivotal in highlighting the communicative challenges faced by these populations and offers practical solutions for improving oral communication competencies. The insights gained are instrumental in devising educational initiatives and workshops aimed at equipping local business owners with essential skills. Thus, it would foster local product promotion and contribute to economic development.